Review of pediatric encephalitis and encephalopathy cases following immunization reported to the Canadian Immunization Monitoring Program Active (IMPACT) from 1992 to 2012. Issue 28 (9th June 2020) - Tam, Jennifer; Tran, Dat; Bettinger, Julie A.; Moore, Dorothy; Sauvé, Laura; Jadavji, Taj; Tan, Ben; Vaudry, Wendy; Halperin, Scott A.; Top, Karina A.; ,
Highlights: We analyzed encephalopathy/encephalitis cases following immunization. 57 acute and 4 chronic cases were reported via active surveillance over 21 years. 69% of cases had an alternate cause for encephalopathy/encephalitis than vaccination. Encephalopathy/encephalitis following vaccination is most often non-vaccine related. Abstract: Background: Neurological adverse events following immunization (AEFI) remain poorly characterized. Our objective was to describe pediatric acute and chronic encephalopathy and encephalitis cases following immunization reported via active sentinel surveillance from 1992 to 2012. Methods: This case series provides a descriptive analysis of encephalopathy/encephalitis admissions reported to the Canadian Immunization Monitoring Program ACTive (IMPACT). Acute cases were reported if symptom onset (seizures, decreased level of consciousness, change in mental status) occurred 0–7 days after tetanus or pertussis-containing vaccines, 0–15 days after other inactivated vaccines, or 5–30 days after live vaccines. Chronic cases of subacute sclerosing panencephalitis or subacute progressive rubella encephalitis were reported at any interval after vaccination. Clinical data were examined to identify possible causes for encephalopathy/encephalitis other than vaccination. Results: Sixty-one cases of encephalopathy/encephalitis following immunization were reported to IMPACT over 21 years; 57 (93.4%) were classified as acute and 4 (6.6%) were chronic cases of subacute sclerosing panencephalitis. Most patients (73.8%) were previously healthy and immunocompetent. The vaccines most frequently administered prior to presentation were diphtheria-tetanus-pertussis, measles-mumps-rubella, and influenza. At discharge, 38 patients (62.3%) had normal neurological status or were expected to recover. Forty patients (70.2%) with acute encephalopathy/encephalitis had a more likely alternate etiology besides vaccination based on neuroimaging, symptoms suggestive of infection, laboratory-confirmed non-vaccine-related infection, or clinical diagnosis. No cases of encephalitis were causally associated with pertussis or influenza vaccines. Two patients (50%) with subacute sclerosing panencephalitis had known wild-type measles infection prior to immunization. Three deaths were reported during hospitalization (4.9%); all were acute encephalitis/encephalopathy cases and none were confirmed to be vaccine-related. Conclusions: Encephalopathy/encephalitis following immunization remains a rare but serious adverse event. Most cases had another more likely etiology than vaccination. Continued monitoring and analysis of AEFI is paramount to ensure the safety of immunization programs.